A review on the susceptor assisted microwave processing of materials. (15th February 2016) - Bhattacharya, Madhuchhanda; Basak, Tanmay
Abstract: Microwave processing has received significant attention based on the energy efficient volumetric processing. The internal heat generation during the microwave heating unleashes the heat transfer limitations of the conventional furnaces and thus, the microwave processing can be performed at much faster rates than the conventional furnaces. Susceptors further accelerate the microwave processing via providing a two-way heating with reduced heat losses from the surface of the material. In addition, the rapid initial heating via susceptors becomes the key factor to execute the energy efficient microwave processing for the poorly microwave absorbing materials. These characteristics have been massively exploited for various applications (material processing, synthesis and waste treatments) over the last few decades and this review evaluates those processing characteristics with an emphasis on the energy efficiency. Till date, the advancement of the susceptor assisted microwave processing is primarily based on the experimental trials and this review brings together various case studies so that the readers can have a clear idea about the current status in each field of applications. This can be of immense help not only to select the appropriate susceptor, but also to select the future research direction for the advancement of the energy efficient processing. Highlights: Susceptor assisted hybrid microwave processing has been reviewed. Energy efficiency of the hybrid heating has been analyzed for various applications. The applications include material processing, synthesis and waste treatment. The role of susceptors on the energy efficient material processing is highlighted. The enhancement of the processing via the susceptors has been reported.